Effect of H2 treatment in a mouse model of rheumatoid arthritis‐associated interstitial lung disease. Issue 10 (19th August 2019) - Terasaki, Yasuhiro; Terasaki, Mika; Kanazawa, Satoshi; Kokuho, Nariaki; Urushiyama, Hirokazu; Kajimoto, Yusuke; Kunugi, Shinobu; Maruyama, Motoyo; Akimoto, Toshio; Miura, Yoko; Igarashi, Tsutomu; Ohsawa, Ikuroh; et al.
Abstract: Rheumatoid arthritis (RA)‐associated interstitial lung disease (ILD), a primary cause of mortality in patients with RA, has limited treatment options. A previously established RA model in D1CC transgenic mice aberrantly expressed major histocompatibility complex class II genes in joints, developing collagen II‐induced polyarthritis and anti‐cyclic citrullinated peptide antibodies and interstitial pneumonitis, similar to those in humans. Molecular hydrogen (H2 ) is an efficient antioxidant that permeates cell membranes and alleviates the reactive oxygen species‐induced injury implicated in RA pathogenesis. We used D1CC mice to analyse chronic lung fibrosis development and evaluate H2 treatment effects. We injected D1CC mice with type II collagen and supplied them with H2 ‐rich or control water until analysis. Increased serum surfactant protein D values and lung densities images were observed 10 months after injection. Inflammation was patchy within the perilymphatic stromal area, with increased 8‐hydroxy‐2ʹ‐deoxyguanosine‐positive cell numbers and tumour necrosis factor‐α, BAX, transforming growth factor‐β, interleukin‐6 and soluble collagen levels in the lungs. Inflammatory and fibrotic changes developed diffusely within the perilymphatic stromal area, as observed in humans. H2 treatment decreased these effects in the lungs. Thus, this model is valuable for studying the effects of H2 treatment and chronic interstitial pneumonia pathophysiology in humans. H2 appears to protect against RA‐ILD by alleviating oxidative stress.